PENGEMBANGAN FORMULA ENTERAL BERBASIS TEPUNG LABU KUNING (Cucurbita moschata) DAN TEPUNG PUTIH TELUR (Albumen) UNTUK PASIEN GAGAL GINJAL KRONIK PREDIALISIS DEVELOPMENT OF AN ENTERAL FORMULA BASED ON PUMPKIN FLOUR (Cucurbita moschata) AND EGG WHITE FLOUR - Putri, Melani Yuda; Yenny, Moviana (Poltekkes Kemenkes Bandung, 2024)
ABSTRACT This study aims to determine the effect of different formulations of pumpkin flour and egg white flour on the quality of low-protein enteral food for CKD patients